EFFECT OF LEADERSHIP AND REMUNERATION ON WORK EFFECTIVENESS (Case Study at The Research and Development Agency of The Supreme Court) - Indrakusumah, Faruq; Rahmawati, Rita; Sudarsa, Agus Suarman (Administratie: Jurnal Administrasi Publik, 2020)
The existence of bureaucratic reform at the Supreme Court in general and the Research and Development Agency, in particular, requires more performance for the organization to achieve its goals. Bureaucratic Reform is divided into 3 (three) groups, namely: drivers (directors/controllers), system and enablers (systems and drivers), and results (results). Furthermore, the involvement of all organizational components is needed to support bureaucratic reform. The research objectives to be obtained in the research conducted by the author include: To determine the effect of leadership and remuneration on work effectiveness at the Research and Development Agency of the Supreme Court, either partially or simultaneously. The population in this study is the staff of the Supreme Court's Research and Development Agency, whose address is at Jalan Cikopo Selatan as many as 132 people. The number of samples was taken based on the Slovin formula. After calculating the sample obtained as many as 57 respondents. The data analysis tool uses multiple linear regression. The results of leadership research have a significant effect on the effectiveness of employees' work at the Supreme Court's Education and Training Research and Development Agency, the effect is positive, which means that if the leadership of the Supreme Court's Education and Training Research and Development Agency is improved, the work efficiency of employees will increase. Remuneration has a significant effect on the effectiveness of employees' work at the Research and Development Agency of the Supreme Court, the effect is positive, which means that if the remuneration on the effectiveness of employees' work at the Research and Development Agency of the Supreme Court is increased, the effectiveness of the employee's work will increase. Leadership and remuneration together have a significant effect on the effectiveness of employees' work at the Research and Development and Training Agency of the Supreme Court.